2010
DOI: 10.1097/mpg.0b013e3181d1b013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Intestinal Inflammation in Patients With Cystic Fibrosis

Abstract: Small bowel mucosal pathology may be detected using CE in most of the patients with CF. The high fecal calprotectin levels found are suggestive of mucosal inflammation, which may correlate with the CE findings. Additional study is required to examine the possible relation of these mucosal lesions, which may be part of a newly identified enteropathy associated with CF, with persistent intestinal malabsorption in many of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
156
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(175 citation statements)
references
References 30 publications
11
156
2
6
Order By: Relevance
“…A conventional endoscopic study showed that the CF duodenum was morphologically normal but there were increased levels of several inflammatory markers in biopsied tissue (Raia et al 2000). More recent work using video-equipped capsule endoscopy showed that morphological abnormalities including edema, erythema, mucosal breaks, and ulcerations occur in the jejunum and ileum in .60% of CF patients (Werlin et al 2010). That study also reported significant elevations of fecal calprotectin (a neutrophil secretory product) in many CF patients, consistent with intestinal inflammation.…”
Section: Inflammationsupporting
confidence: 56%
“…A conventional endoscopic study showed that the CF duodenum was morphologically normal but there were increased levels of several inflammatory markers in biopsied tissue (Raia et al 2000). More recent work using video-equipped capsule endoscopy showed that morphological abnormalities including edema, erythema, mucosal breaks, and ulcerations occur in the jejunum and ileum in .60% of CF patients (Werlin et al 2010). That study also reported significant elevations of fecal calprotectin (a neutrophil secretory product) in many CF patients, consistent with intestinal inflammation.…”
Section: Inflammationsupporting
confidence: 56%
“…Pancreatic insufficiency is seen in about 80-85% of cystic fibrosis (CF) patients [1]. Though enzyme treatment dramatically improves the condition, gastrointestinal (GI) symptoms and severe obstructive conditions such as distal intestinal obstruction syndrome are common with great impact on patients' quality of life [2].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of FC measurement is the stability in stool samples of up to 7 days at room temperature which makes stool collection and transportation simple and feasible 3. Increased FC concentrations have been found in several inflammatory gastrointestinal (GI) diseases including gastric cancer, colorectal cancer and colonic polyps, as well as in chronic inflammatory bowel disease (IBD),3 allergic colitis,5 necrotising enterocolitis6 and cystic fibrosis 7. Increased FC concentrations can be considered as inflammation specific, but not disease specific.…”
Section: Introductionmentioning
confidence: 99%